(untitled) (International journal of artificial intelligence, 2026)
This article explores the theoretical and practical foundations of forming cognitive competencies in future primary school teachers within an innovative pedagogical environment. The study analyzes the role of integrative approaches, interactive technologies, and interdisciplinary learning in enhancing cognitive development. The results of experimental work demonstrate that the implementation of innovative pedagogical strategies significantly improves students’ analytical thinking, problem-solving abilities, and reflective skills.